Pengembangan E-Modul Berbasis Learning Content Development System Pokok Bahasan Pola Bilangan SMP - Ula, Iin Rahmatul; Fadila, Abi (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to produce instructional materials in the form of electronic module based learning content development system on the matter of pattern number. This research method is Research and Development (R & D) based on ADDIE model. Assessment of material experts on the learning media is included in the category of